Substitutability between drugs, innovation and growth in the pharmaceutical industry - Vale, S.; de Mello-Sampayo, F.; Camões, F. (10th Eurasia Business and Economics Society, 2013)
This paper establishes a relationship between the elasticity of demand for pharmaceutical intermediates and the growth rate for these interme- diates variety. We build a model that contains two sectors, one nal good sector producing treatments, and one intermediate goods sector produc- ing a dierentiated input used in the nal treatment. The eects on the medicaments varieties' growth rate of the introduction of a scal in- strument over pharmaceutical producers' pro ts are discussed. When the scal instrument is a tax over intermediate rms' pro ts, R&D by rms in the pharmaceutical goods sector results in positive growth provided pro- vided there exists enough substitutability among intermediates assured by a patent system. Otherwise, a subsidy over pharmaceutical rms' pro ts should be considered to generate positive growth of innovation in medica- ments